The Effects of Cuboid Particle Scattering on Reflected Light Phase Curves: Insights from Laboratory Data and Theory - Colin D. Hamill; Alexandria V. Johnson; Matt Lodge; Peter Gao; Rowan Nag; Natasha Batalha; Duncan A. Christie; Hannah R. Wakeford (The Astrophysical Journal, 2025)
Understanding the optical properties of exoplanet cloud particles is a top priority. Many cloud condensates form as nonspherical particles and their optical properties can be very different from those of spheres. In this study, we focus on KCl particles, which likely form as cuboids in warm ( T = 500–1000 K) exoplanet atmospheres. We compare the phase functions (at 532 nm wavelength) of KCl particles computed with Mie theory, the two-term Henyey–Greenstein (TTHG) approximation, laboratory data, and the discrete dipole approximation (DDA). Mie theory assumes scattering from spheres, while TTHG functions are used to approximate cloud scattering in two-stream radiative transfer models like PICASO . Laboratory measurements and DDA allow for a robust understanding of scattering from cuboid and deformed cuboid particle shapes. We input these phase functions into PICASO using cloud distributions from the cloud model Virga , to determine how different phase functions can impact the reflected-light intensities of the benchmark sub-Neptune, GJ 1214b. Simulated reflected light phase curves of GJ 1214b produced using the TTHG, laboratory, and DDA phase curves differ by less than 3 ppm. Our findings suggest that TTHG phase functions may be useful for approximating the scattering intensity of certain cuboid and irregular particle shapes. Future work should expand upon the wavelengths and particles considered to better determine when scattering approximations, like TTHG, may be useful in lieu of more accurate, but time-consuming laboratory measurements and/or nonspherical scattering theory.